The phenomenon of religiosity in modern Kazakhstan (the sociological view) - Shaukenova, Z. K.; Burova, E. E.; Bektenova, M. K. (Eurasian Journal of Religious Studies, 2016)
Religion in contemporary society acts as a strategic resource, in the global, regional, and national and state developments. Religiosity becomes an epiphenomenon, not only in the context of its beingness as a significant characteristic of the mentality, but also as an institutional system. Manifesting itself as one of the fundamental characteristics of mentality religiosity points to the involvement of individuals, groups and society as a religion as the institutional framework governing the life of the communities with the help of symbolic belief systems corresponding ritual practices and traditions.The study of the states, the dynamics and the trends of religiosity helps to understand the trends of societal changes, which is extremely important in the development of mechanisms and strategies of social development.
Keywords: State policy on religion; indicators of religiosity; worldview; monitoring of religiosity; model of religiosity